Newer treatments of psoriasis regarding IL‐23 inhibitors, phosphodiesterase 4 inhibitors, and Janus kinase inhibitors - Wcisło‐Dziadecka, Dominika; Zbiciak‐Nylec, Martyna; Brzezińska‐Wcisło, Ligia; Bebenek, Katarzyna; Kaźmierczak, Agata (Dermatologic therapy, 2017)
The rapid progress of genetic engineering furthermore opens up new prospects in the therapy of this difficult‐to‐treat disease. IL‐23 inhibitors, phosphodiesterase 4 (PDE4) inhibitors, and Janus kinase (JAK) inhibitors are currently encouraging further research. Two drugs which are IL‐23 inhibitors are now in phase III of clinical trials. The aim of the action of both drugs is selective IL‐23 inhibition by targeting the p19 subunit. Guselkumab is a fully human monoclonal antibody. Tildrakizumab is a humanized monoclonal antibody, which also belongs to IgG class and is targeted to subunit p19 of interleukin 23 (IL‐23). Phosphodiesterase inhibitors exert an anti‐inflammatory action and their most common group is the PDE4 family. PDE4 inhibits cAMP, which reduces the inflammatory response of the pathway of Th helper lymphocytes, Th17, and type 1 interferon which modulates the production of anti‐inflammatory cytokines such as IL‐10 interleukins. The Janus kinase (JAK) signaling pathway plays an important role in the immunopathogenesis of psoriasis. Tofacitinib suppresses the expression of IL‐23, IL‐17A, IL‐17F, and IL‐22 receptors during the stimulation of lymphocytes. Ruxolitinib is a selective inhibitor of JAK1 and JAK2 kinases and the JAK‐STAT signaling pathway. This article is a review of the aforementioned drugs as described in the latest available literature.